ANALISIS BERPIKIR KRITIS PESERTA DIDIK SMA PADA MATERI PEMANASAN GLOBAL MELALUI TES BERBASIS MASALAH - Lailatul Fajriati; Oka Saputra (STKIP Subang, 2026)
This study aims to analyze students' critical thinking skills on global warming through problem-based tests. The research method used was quantitative descriptive with class XI subjects selected through purposive sampling techniques involving 32 students from class XI 1. The research instrument is in the form of a set of problem-based tests developed based on Facione's critical thinking indicators which include interpretation, analysis, evaluation, inference, and explanation and is equipped with a non-test questionnaire as a support for the analysis. The results of the study show that the average achievement of critical thinking skills of SMAN 17 Surabaya students is at 49% in the